Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.vpoa.2020.100029
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the biology, diagnosis and immune response to Dirofilaria repens in the canine host

Abstract: Highlights Antibody response to D. repens in dogs develops before the onset of patency. Wolbachia and D. repens antibodies had peaks of OD values on Days 220, 245, 281. The specificity of IgG ELISA against D. repens and Wolbachia must be evaluated. If microfilarial counts are too l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Diro laria somatic antigens ELISA were successfully used in several previous studies [28][29][30][31] , and we showed it might be applied to diagnose cases without presence of micro lariae in the blood. The length of prepatent period varies depending on the study.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Diro laria somatic antigens ELISA were successfully used in several previous studies [28][29][30][31] , and we showed it might be applied to diagnose cases without presence of micro lariae in the blood. The length of prepatent period varies depending on the study.…”
Section: Discussionmentioning
confidence: 90%
“…Petry et al 32 reported that in experimentally infected dogs, prepatency lasts 169 to even 256 days post infection (dpi). In contrast, the others report patency beginning at 220-281 dpi, con rmed by molecular method and at 245-288 dpi established by Knott's test 31 . Thus, in the rst 5-9 months of infection, both described methods (Knott and PCR tests) are ineffective.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The relative high specificity of commercial Dirofilaria immitis antigen tests is in contrast to the cross-reactive nature of antibody tests historically used for D. immitis [ 6 , 7 ] and more recently described as a diagnostic approach examining human exposure to Dirofilaria sp. [ 8 , 9 ] and potential application for D. repens infected dogs [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dirofilaria repens, an agent that generally causes subclinical infections, is responsible for subcutaneous dirofilariosis in dogs and it is frequently linked with the presence of adults in subcutaneous tissues, representing the main cause of human dirofilariosis. The clinical signs of this infection in dogs include pruritus, localized alopecia, or cutaneous ulceration [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%